ANALISIS PENERIMAAN DAN PENGGUNAAN APLIKASI OVO DENGAN MENGGUNAKAN UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY (UTAUT) DI KOTA DENPASAR - Gusi Putu Lestara Permana; Luh Putu Kristiari Dewi (Jurnal Ilmiah Akuntansi & Bisnis, 2019)
Analysis of Acceptance and Use of OVO Applications Using Unified Theory of Acceptance and Use of Technology in Denpasar CityThis study aims to determine the success of the acceptance and use of OVO applications by using the Unified Theory of Acceptance and Use of Technology (UTAUT) in Denpasar City. The UTAUT model in this study uses performance expectancy, effort expectancy, social influence, facilitating conditions, behavioral intention, use behavior, experience and voluntariness of use. The data acquisition in this study was processed using Partial Least Squares (PLS). The  samples  were 125 samples. Sources of data in this study are primary data sources sourced from questionnaire results that have been filled out by respondents. The research and testing instrument used is the outer model, while the data analysis technique used is the inner model and hypothesis testing.Based on the results, the hypothesis shows that performance expectations, effot expectations, social influences, facilitating conditions is positive towards behavior intentions. The behavioral intention is stated positively towards the use of behavior. However, the moderator variables that are declared not binding relations the independent variables and the dependent variable when receiving and using OVO applications in Denpasar.Keywords: UTAUT Model, e-money, OVO application